New peptides with immunomodulatory activity in macrophages and antibacterial activity against multiresistant Staphylococcus aureus (2017)
Staphylococcus aureus infections are a common concern worldwide due to the increasing number of bacterial strains with multiresistant properties to existing antibiotics, incrementing the need for novel therapy approaches for their treatment. This study evaluated the antibacterial and immunomodulatory activity of eight new peptides as the basis for the search of new antibacterial and therapeutic agents for topic prevention and treatment against S. aureus infections. The methodology consisted of the in silico characterization of the eight peptides in order to identify their antimicrobial peptide characteristics. Following, antibacterial activity microdilution assays were performed with the eight new peptides individually and in combination. Furthermore, the cytotoxic activity of the peptides was evaluated against fibroblasts, monocytes and macrophages. Finally, immunomodulatory activity assays were performed with three of the peptides (GF, AT and AA) in macrophages and under three scenarios: non-stimulation, E. coli LPS stimulation and S. aureus lysate stimulation. Results showed that the GF, AT and AA peptides individually showed the best antibacterial activity and the combination of the eight peptides was able to decrease the bacterial growth of the clinically isolated strains more than the individual antibiotic controls. In addition, the peptides, except for LK, AT and the peptide combination, did not present cytotoxic activity against the cell lines tested. Finally, AA, GF and RN peptides presented immunomodulatory activity in macrophages by displaying different profiles of enhancement and diminution of four cytokines. This activity depended on the stimulation which the macrophages were exposed to. Taken together, these results demonstrate the potential of these peptides to be used in further studies as novel antimicrobial molecules for the prevention and treatment of S. aureus infections.